Nonlinear piezoelectric plate framework for aeroelastic energy harvesting and actuation applications - De Carvalho Dias, Jose Augusto (2020)
The use of piezoelectric materials in various applications, including the development of bio-inspired structures, vibration control, energy harvesting, among others, has been investigated by several researchers over the last few decades. In most cases, linear piezoelectricity is assumed in modeling and analysis of such systems. However, the recent literature shows that non-linear manifestations of piezoelectric materials are relevant and can modify the electromechanical behavior especially around the resonance. This work extends the investigation of non-linear piezoelectricity, by adding geometric nonlinearities and aerodynamic effects, to aeroelastic problems such as wind energy harvesting. A piezoaeroelastic model that combines a non-linear coupled finite element model and the doublet lattice model of unsteady aerodynamics is presented. The electromechanically coupled finite element model includes the non-linear behavior of piezoelectric material under weak electric fields. Model predictions are validated by experimental data for 1) a double bimorph actuation case and 2) a vibration based energy harvesting case. Later, the piezoaeroelastic behavior of a generator plate-like wing for wind energy harvesting is numerically investigated when linear as well as non-linear piezoelectricity is considered. The experimentally validated geometrically and materially non-linear framework presented here is applicable to both energy harvesting and actuation problems in the presence of air flow.